2013
DOI: 10.3390/w5030852
|View full text |Cite
|
Sign up to set email alerts
|

Framing Scenarios of Binational Water Policy with a Tool to Visualize, Quantify and Valuate Changes in Ecosystem Services

Abstract: Abstract:In the Santa Cruz Watershed, located on the Arizona-Sonora portion of the U.S.-Mexico border, an international wastewater treatment plant treats wastewater from cities on both sides of the border, before discharging it into the river in Arizona. These artificial flows often subsidize important perennial surface water ecosystems in the region. An explicit understanding of the benefits of maintaining instream flow for present and future generations requires the ability to assess and understand the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…As a watershed is urbanized and vegetation is replaced by impervious surfaces, the area where infiltration to groundwater can occur is greatly reduced, compromising soil-water storage capability. As the model used is uncalibrated, we feel it important to note that usual calibration for this river system and nearby rivers would start with removing most of the lateral flow component [14,16,53,54,57,65,66]. This is because arid lands do not support a great amount of soil water-moisture transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a watershed is urbanized and vegetation is replaced by impervious surfaces, the area where infiltration to groundwater can occur is greatly reduced, compromising soil-water storage capability. As the model used is uncalibrated, we feel it important to note that usual calibration for this river system and nearby rivers would start with removing most of the lateral flow component [14,16,53,54,57,65,66]. This is because arid lands do not support a great amount of soil water-moisture transfer.…”
Section: Discussionmentioning
confidence: 99%
“…SWAT has been applied to predict the effect of land use, management practices, and climate change on water, sediment, and agricultural chemical yields in small-to large-scale watersheds with varying soils, land use, and management over extended periods of time [48,49]. It is oft used in assessing erosion control, non-point source pollution control, and best management in watersheds [13,14,16,[50][51][52][53][54].…”
Section: Hydrological Model Applicationmentioning
confidence: 99%
“…Previous flood vulnerability assessments incorporated climate uncertainties (Norman et al 2010a) and calibration analysis for the region, accentuated its importance for watershed modeling, but suggested that is not essential for examining alternative future scenarios due to climate variability (Niraula et al 2012;Niraula et al 2015). Other relevant studies include a modeling framework for water resources planning for the Santa Cruz River (Shamir et al 2007a, b) and an analysis of binational water policy scenarios to determine the impact of effluent discharge reductions to ecosystem services (Norman et al 2013 (CONAGUA 2015(CONAGUA , 2018).…”
Section: Previous Workmentioning
confidence: 99%
“…Several studies have analyzed the uncertainties associated with the ownership and reuse of sewage and effluent from Nogales, Sonora and Nogales, Arizona (Sprouse and Atondo 2004;Norman et al 2013;Prichard and Scott 2014); the impact of increased groundwater demands (Erwin 2007;Nelson 2007;Shamir et al 2007a;Shamir 2017); and the impact of climate uncertainties within different TSCA regions (Norman et al 2010a, b;Scott et al 2012;Shamir et al 2015;. Although these studies address some of the main issues concerning land and water management in the area, none of them provide a comprehensive analysis for the effluent-dominated stretch of the TSCA.…”
Section: Introductionmentioning
confidence: 99%
“…Mexico's portion of the discharge is approximately 55 percent and could be diverted away from the NIWTP and the river if Mexico decides such action would be in its best interest. This action would likely reduce flow in the river, with a negative impact on the downstream riparian ecosystem in Arizona [46].…”
Section: Settingmentioning
confidence: 99%